Study on Antioxidant Activity of Purple Sweet Potato (Ipomoea batatas) Juice Fermented with Lactobacillus plantarum B1765 - Fitria, Marcella Nur; Wikandari, Prima Retno (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Purple sweet potatoes are a source of anthocyanins, which are antioxidants. However, the anthocyanin compounds in purple sweet potatoes are naturally bound in glycosidic form, so their potential as antioxidants is still limited. Fermentation is one method that can be used to degrade glycosidic bonds to liberate free phenolics so that it can increase the antioxidant potential of purple sweet potato. This research aims to study the growth of lactic acid bacteria (LAB), pH, total titratable acid (TAT), phenolic content, anthocyanin content, and antioxidant activity of sweet potato juice (Ipomoea batatas) fermented with Lactobacillus plantarum B1765 starter culture for 0.2, 4,6,8,10,12 and 14 hours. Total LAB was measured using the Total Plate Count (TPC) method, pH was measured using a pH meter, TAT was measured using acid-base titration, total phenolic content (TPC) was measured using the Folline-Ciocalteu method, anthocyanin content used the differential pH method and antioxidant activity was measured using the radical scavenging method 2, 2-diphenyl-1-picrylhydrazyl (DPPH) which is expressed in IC50 values. The results showed that fermentation time affected (p<0.05) total LAB, pH, TAT, phenols, anthocyanin levels, and antioxidant activity in purple sweet potato juice. Total BAL increased to reach an optimum of 2.6 x 108 CFU/mL within 6 hours. However, until the end of fermentation for 14 hours, there was still a decrease in pH to 3.73, an increase in TAT reaching 0.426%, an increase in total phenolics up to 324.21 mg GAE/g, a reduction in anthocyanin levels (13.68 mg/L) and an increase in antioxidant activity with an IC50 of 47 .05 ppm which is classified as very strong. This product meets the Indonesian National Standards for fermented drinks and can potentially be a source of antioxidants.